A novel pyrrolidine-chalcone derivative exhibits synergistic anti-cervical cancer activity by dual-targeting MDM2-p53 axis and ferroptosis pathway - Xiamuxi, Hainimu; Deng, XinYi; Ablise, Mourboul; Yan, Tong; Imam, Madina; Wang, Yu; Zu, MingHui; Wumaier, Wutiekuer (Frontiers in Pharmacology, 2026)
IntroductionCervical cancer remains a serious threat to women’s health, driving the need for effective and low-toxicity therapeutics. This study designed novel pyrrolidine-chalcone derivatives targeting the MDM2-p53 interaction.MethodsA series of compounds were synthesized and evaluated for cytotoxicity against cervical cancer (HeLa, SiHa, C33A) and normal (H8) cells via CCK-8. The lead compound B1 was further analyzed for p53 pathway activation, apoptosis, and ferroptosis markers (ROS, GSH, MDA, Fe2+) using western blot, flow cytometry, and assay kits.ResultsCompound B1 showed potent, nanomolar cytotoxicity (IC50 = 0.22, 0.24, and 0.95 μM for HeLa, SiHa, and C33A, respectively) with low toxicity to H8 cells. B1 activated p53 by downregulating MDM2, inducing cell cycle arrest and apoptosis. Simultaneously, it triggered ferroptosis via ROS accumulation, GSH depletion, elevated MDA and Fe2+, and suppression of SLC7A11/GPX4.DiscussionB1 is a promising dual-mechanism lead compound against cervical cancer, concurrently activating p53 and ferroptosis, warranting further investigation.